Pengaruh Gaya Mengajar Guru dan Kepuasan Belajar Siswa Terhadap Hasil Belajar Siswa (Studi Kasus pada SMK Triyasa Surabaya) - Diahvitaloka, Tita Andira; Iswati (Jurnal EMT KITA, 2024)
This problem examines (1) Does the teacher's teaching style influence student learning outcomes at Triyasa Vocational School, Surabaya? (2) Does student learning satisfaction influence student learning outcomes at Triyasa Vocational School, Surabaya? (3) Do teachers' teaching styles and student learning satisfaction influence student learning outcomes at Triyasa Vocational School, Surabaya? The aim is to determine the influence of teacher teaching style and student learning satisfaction on learning outcomes with correlation research. Data collection uses questionnaires/questionnaires and documentation by taking samples using the Proportionate random sampling technique. Data analysis uses multiple linear regression analysis. The results of the research show that teaching style at t count 0.145 ≤ t table 2.016, learning satisfaction at t count 1.160 ≤ t table 2.016, teaching style and student learning satisfaction at F count 1.086 and Sig 0.347 ≥ Sig 0.05 (5%), the variables tested have no influence on student learning outcomes.